2009
DOI: 10.1542/peds.2008-2445
|View full text |Cite
|
Sign up to set email alerts
|

Association of Family History of Autoimmune Diseases and Autism Spectrum Disorders

Abstract: Associations regarding family history of type 1 diabetes and infantile autism and maternal history of rheumatoid arthritis and ASDs were confirmed from previous studies. A significant association between maternal history of celiac disease and ASDs was observed for the first time. The observed associations between familial autoimmunity and ASDs/infantile autism are probably attributable to a combination of a common genetic background and a possible prenatal antibody exposure or alteration in fetal environment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
261
4
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(279 citation statements)
references
References 36 publications
9
261
4
5
Order By: Relevance
“…Individual SNPs and haplotypes were tested for association with ASD. Additionally, the relationship between diabetes, autism and CD38 [70], as well as the use of CD38 as a disease marker [71], suggests that it would also be worthwhile to explore CD38 expression in immune cell lines derived from ASD patients. These considerations prompted us to measure CD38 gene expression in lymphoblastoid cell lines (LBC) derived from both ASD subjects and unaffected parents.…”
Section: Cd38 and Autism Spectrum Disordersmentioning
confidence: 99%
“…Individual SNPs and haplotypes were tested for association with ASD. Additionally, the relationship between diabetes, autism and CD38 [70], as well as the use of CD38 as a disease marker [71], suggests that it would also be worthwhile to explore CD38 expression in immune cell lines derived from ASD patients. These considerations prompted us to measure CD38 gene expression in lymphoblastoid cell lines (LBC) derived from both ASD subjects and unaffected parents.…”
Section: Cd38 and Autism Spectrum Disordersmentioning
confidence: 99%
“…In seven of these studies, an association between familial autoimmunity and ASD was determined. In all but two of the studies, 2,3 however, the number of subjects was relatively small, and interpretation is compounded by the fairly low rate at which autoimmune diseases occur in the general population 4 ( Table 1). …”
mentioning
confidence: 99%
“…To date, the majority of studies have used self-reporting questionnaires, which are prone to inaccuracy and potential over-reporting. However, from a large populationbased study (nearly 700,000 participants) in which both the ASD diagnosis and family history of autoimmune disease were obtained from medical records and not from surveys, Atladóttir et al 2 found that some autoimmune disease were more common in parents of children with ASD. That study indicated increased rates of rheumatoid arthritis and celiac disease in mothers of children with ASD, and a higher rate of the autoimmune condition type 1 diabetes in both mothers and fathers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Recent research on postnatal immune issues identify various serum antibodies, as well as cord blood neurotrophins and cytokine levels as potential factors. [12][13][14][15][16][17] Atladottir et al 18 found an increased risk of ASDs in children with a maternal history of rheumatoid arthritis and celiac disease. Also, increased risk of infantile autism was observed for chil-dren with a family history of type 1 diabetes.…”
Section: Part 1: Immune System and Autism: Defining The Relationshipmentioning
confidence: 99%